Analisis Keterlambatan Pengiriman Unit Menggunakan Metode Six Sigma (Studi Kasus Pada PT XYZ) - Duma Joanna Rotua Simanjuntak; Anggoro Prasetyo Utomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PT. XYZ is a network providing sales, maintenance, repair and spare parts for Toyota, which is fully owned by PT. Astra International Tbk. The main problem PT. XYZ is delivery delays. In 2023, out of 11,208 deliveries, 2,098 units were delayed, resulting in a delay rate of 18.72%. According to PT. XYZ, delays are acceptable if they are below 15%; above that, they are unacceptable. PT. XYZ needs to analyse the factors causing these delays using the Six Sigma method with the DMAIC approach. The aim is to identify the causes of delays, determine the Six Sigma level and propose improvements. The research identified three main issues: pre-delivery inspection failures with 83.76% due to external damage; administrative process obstacles with 90.05% due to vehicle registration issues; and inbound stock overload with 100% due to PDC overload. The average sigma level is 3.27 σ, rounded to 3 σ. The main causes are employee negligence and contamination during storage at the PDC. Five improvement proposals are being implemented: mandatory K3 and SIO certification for operators, SOPs for unit storage on trucks and at the PDC, use of full-cover unit protection and use of triple-layer protective material. By implementing these solutions, the company can address the issues that cause delivery delays.